Growth performance and rumen morphometrics of Nellore and ½ Angus/Nellore feedlot cattle adapted over 9 and 14 days to high-concentrate diets - Watanabe, Daniel Hideki Mariano [UNESP]; Bertoldi, Gustavo Perina [UNESP]; dos Santos, Anderson Augusto [UNESP]; da Silva Filho, Wilson Inacio [UNESP]; de Oliveira, Lucas Felipe Rebeschini [UNESP]; Pinto, Ana Carolina Janssen [UNESP]; Ceola Stefano Pereira, Murillo [UNESP]; Estevam, Daniela Dutra [UNESP]; Squizatti, Mariana Martins [UNESP]; Pinheiro, Rafael Silvio Bonilha [UNESP]; Millen, Danilo Domingues [UNESP] (Wiley, 2021)
The objective of this study was to evaluate the effects of adapting Nellore and ½ Angus/Nellore (AN) feedlot cattle over periods of 9 and 14 days to high-concentrate diets on performance, feeding behaviour, carcass traits and rumen morphometrics. Seventy-two yearling bulls (313.5 kg ± 24.5), 36 Nellore and 36 AN, were randomly allocated in 24 pens (3 animals/pen; 24 m2 and 2.0 m of bunk space/animal) according to a randomized complete block design with a 2 × 2 factorial arrangement of treatments as follows: Nellore adapted for 9 days, Nellore adapted for 14 days, AN adapted for 9 days, and AN adapted for 14 days. Each treatment was composed by 6 pens (considered the experimental unit in this study). The adaptation lasted either 9 or 14 days and consisted of 3 step-up diets. Therefore, yearling bulls received the finishing diet containing 86% concentrate either on day 10 or 15 of the study, which lasted 89 days taking into account adaptation and finishing periods. Cattle were slaughtered in a commercial abattoir, and two 1-cm2-rumen fragments, one from cranial and another from ventral sac, were collected. The AN cattle outperformed Nellore in terms of average daily gain (1.71 kg/day vs. 1.27 kg/day, p < 0.01), gain:feed ratio (0.137 kg/kg vs. 0.127 kg/kg, p = 0.02) and hot carcass weight (243.64 kg vs. 228.98 kg, p < 0.01). No main effect of the adaptation period was observed for any of the feedlot performance and carcass traits variables evaluated. Compared to feedlot cattle adapted for 9 days, feedlot cattle adapted for 14 days sorted against long (0.68 vs. 0.91, p < 0.01) and for fine particles (1.04 vs. 1.00, p = 0.01). An interaction (p < 0.01) of genotype and adaptation period was observed for rumenitis, where Nellore bulls adapted for 14 days presented the highest scores. In conclusion, there was no evidence that either Nellore or AN cattle benefit from an adaptation period shorter than 14 days.
Keywords: acidosis; behaviour; genotype; rumen; rumenitis